2022
DOI: 10.3389/fnut.2022.794489
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Prognostic Nutritional Index in Patients With Colorectal Cancer Undergoing Surgical Treatment

Abstract: BackgroundTo investigate the relationship between prognostic nutritional index (PNI) and the survival of patients with colorectal cancer (CRC) undergoing surgical treatment.MethodsIn total 1,014 CRC patients who underwent surgical treatment were enrolled. Logistic regression analysis was used to identify the features that influenced postoperative complications in CRC patients. Restricted cubic spline was used to assess the dose-response relationship between PNI and survival in CRC patients. Kaplan-Meier method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…PNI is a simple index developed by Onodera et al, reflecting immune, inflammatory, and nutritional status (39). According to recent studies, PNI significantly correlates with adverse outcomes in various diseases (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Zheng et al reported that a lower PNI is an independent risk factor for higher mortality in patients with respectable esophageal squamous cell carcinoma (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNI is a simple index developed by Onodera et al, reflecting immune, inflammatory, and nutritional status (39). According to recent studies, PNI significantly correlates with adverse outcomes in various diseases (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Zheng et al reported that a lower PNI is an independent risk factor for higher mortality in patients with respectable esophageal squamous cell carcinoma (7).…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic Nutritional Index (PNI) is a simple and objective index of inflammatory and nutrition status derived from serum albumin (ALB) and lymphocyte counts. Recently, PNI has been reported to be an independent prognostic predictor for patients with cancer, stroke, heart disease, chronic kidney disease, acute exacerbation of the chronic obstructive pulmonary disease, sepsis, COVID-19, and autoimmune disease (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, no research has been conducted to examine the relationship between PNI and the prognosis of patients with DLC.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the outcome of cancer patients is determined by many factors, including nutrition status [ 5 ] and anticancer immunity [ 6 ], in addition to the cancer cells themselves; accordingly, it is plausible that prognostic markers could be more reasonable if these factors are comprehensively considered. The prognostic nutritional index (PNI), which is a marker calculated based on serum albumin and lymphocytes, is a robust prognostic indicator in many malignancies, including lung cancer [ 7 ], nasopharyngeal cancer [ 8 ], liver cancer [ 9 ], breast cancer [ 10 ], gastric cancer [ 11 ] and CRC [ 12 , 13 ]. Interestingly, previous studies have indicated that the prognostic efficacy of PNI was superior to that of other inflammation-based prognostic indicators [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prognostic nutritional index (PNI) is obtained by the level of serum albumin and peripheral lymphocytes and is proposed to assess immune-nutritional status ( 20 ). A few studies have shown that low PNI status is associated with an unfavorable prognosis in gastrointestinal and colorectal cancer ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%